Factors associated with early, late, and very late stent thrombosis among patients with acute coronary syndrome undergoing coronary stent placement: analysis from the ATLAS ACS 2-TIMI 51 trial - Chi, Gerald; AlKhalfan, Fahad; Lee, Jane J.; Montazerin, Sahar Memar; Fitzgerald, Clara; Korjian, Serge; Omar, Wally; Barnathan, Elliot; Plotnikov, Alexei; Gibson, C. Michael (Frontiers in Cardiovascular Medicine, 2024)
Background Stent thrombosis (ST) is an uncommon but serious complication of stent implantation. This study aimed to explore factors associated with early, late, and very late ST to help guide risk assessment and clinical decision-making on ST. Methods The analysis included patients who received stent placement for the index acute coronary syndrome (ACS). Cumulative incidence of ST was assessed at 30 days (early ST), 31–360 days (late ST), 361–720 days (very late ST), and up to 720 days. Cox proportional hazards models were used to assess associations between ST and various factors, including patient characteristics [i.e., age, sex, ACS presentation, history of hypertension, smoking, diabetes, prior myocardial infarction (MI), heart failure, prior ischemic stroke, and cancer], laboratory tests [i.e., positive cardiac biomarker, hemoglobin, platelet count, white blood cell (WBC) count], and treatment [i.e., drug-eluting stent (DES) vs. bare-metal stent (BMS) and anticoagulant with rivaroxaban vs. placebo]. Results Among the 8,741 stented patients, 155 ST events (2.25%) occurred by Day 720. The cumulative incidences of early, late, and very late ST were 0.80%, 0.81%, and 0.77%, respectively. After multivariable adjustment, age ≥ 75 [hazard ratio (HR) = 2.13 (95% confidence interval, CI: 1.26–3.60)], a history of prior MI [HR = 1.81 (95% CI: 1.22–2.68)], low hemoglobin level [HR = 2.34 (95% CI: 1.59–3.44)], and high WBC count [HR = 1.58 (95% CI: 1.02–2.46)] were associated with a greater risk of overall ST, whereas DES [HR = 0.56 (95% CI: 0.38–0.83)] and rivaroxaban therapy [HR = 0.63 (95% CI: 0.44–0.88)] were associated with a lower risk of overall ST up to 720 days. Low hemoglobin level and high WBC count were associated with early ST (low hemoglobin: HR = 2.35 [95% CI: 1.34–4.12]; high WBC count: HR = 2.11 [95% CI: 1.17–3.81]). Low hemoglobin level and prior MI were associated with a greater risk of late ST (low hemoglobin: HR = 2.32 [95% CI: 1.26–4.27]; prior MI: HR = 2.98 [95% CI: 1.67–5.31]), whereas DES was associated with a lower risk of late ST [HR = 0.33 (95% CI: 0.16–0.67)]. Age ≥75 years was associated with very late ST. Conclusion The study identified positive and negative associations with early, late, and very late ST. These variables may be useful in constructing risk assessment models for ST. Clinical Trial Registration http://www.clinicaltrials.gov, identifier NCT00809965.